Learning challenge accepted – or not? : Designing T-shirts or demanding personalized garments - Härkki, Tellervo; Oksanen, Johanna; Nuutinen, Ana; Laxström; Karoliina; Kylmänen; Anu; Rönkkö, Marja-Leena (Formakademisk, 2026)
This research studies garment design and production as an integrated learning assignment. In this type of setting, students face – often implicit – design constraints arising from the production phase: time, cost and material resources, but also students' knowledge and skills related to processes, tools, technical structures and technologies. The qualitative data analysis revealed that skill level did not dictate the level of learning challenge undertaken, and that not all novices' work remained limited to simple designs and structures. We discuss tailoring pedagogical practices according to students' needs by balancing familiarity with the challenge and the possibilities of circumstance-based design. We also suggest that, together with students' beliefs about the learnability of design creativity, all constraints should be openly discussed.